Significance and Role of Agriculture Sector in the Socio-Economic Development of Khyber Pakhtunkhwa - Dr. Abdul Hamid; Akram, Naeem (Dialogue Social Science Review (DSSR), 2025)
The Government of Pakistan envisions to make Pakistan self-sufficient in food availability through high yield of agriculture crops and sustained availability round the year. Quality education, applied & focused research is a fundamental requirement to attain this dream. Agriculture has remained the lifeline of Pakistan’s economy since its birth. Agriculture plays a central role in economic development since it accounts for 24% of GDP and 37.4% of employment while more than half of the total population benefits directly or indirectly from agriculture. The growth of agricultural sectors acts as a fundamental force to stimulate economic progress together with employment opportunities and poverty decrease. It plays a significant role in poverty reduction by providing food security to the masses. Agriculture also provides cheap raw material to several value-added industries. However, even though Pakistan is an agrarian economy, agriculture growth and yield is low and is insufficient to fulfill the domestic demand for food for the rapidly growing population.